2014
DOI: 10.1371/journal.pone.0103822
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Molecular Features of Different Macroscopic Subtypes of Colorectal Neoplasms

Abstract: BackgroundColorectal adenoma develops into cancer with the accumulation of genetic and epigenetic changes. We studied the underlying molecular and clinicopathological features to better understand the heterogeneity of colorectal neoplasms (CRNs).MethodsWe evaluated both genetic (mutations of KRAS, BRAF, TP53, and PIK3CA, and microsatellite instability [MSI]) and epigenetic (methylation status of nine genes or sequences, including the CpG island methylator phenotype [CIMP] markers) alterations in 158 CRNs inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 58 publications
1
17
0
Order By: Relevance
“…Previous studies for these tumors showed no mutations in KRAS and high frequencies of p53 expression by immunohistochemistry [ 37 ]. Through PCR-based pyrosequencing, Konda et al have reported that mutation in KRAS and BRAF occurred in 16% and 11% of depressed colorectal neoplasms respectively [ 39 ]. There was a discrepancy between this study and ours.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies for these tumors showed no mutations in KRAS and high frequencies of p53 expression by immunohistochemistry [ 37 ]. Through PCR-based pyrosequencing, Konda et al have reported that mutation in KRAS and BRAF occurred in 16% and 11% of depressed colorectal neoplasms respectively [ 39 ]. There was a discrepancy between this study and ours.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to familial adenomatous polyposis, in which the tumors are pedunculated or semi-pedunculated. Recently, Konda et al reported that the frequency of TP53 mutations was higher in LST-NGs and depressed neoplasms than in polypoid neoplasms, while K-ras mutations were less frequent (12). Furthermore, some reports have noted that the frequency of K-ras mutations is lower in LST-NG than in LST-G and polypoid adenomas.…”
Section: Discussionmentioning
confidence: 99%
“…CpG island DNA methylation occurs early in malignant transformation [ 2 ] and consequently results in silencing of normal tumor-suppressor function and cancer formation, independent of (physiological) age-related methylation. The CIMP subtype exists with and without MSI, both showing distinct morphologic, molecular and most importantly, clinical characteristics [ 3 ]. MSI-high/CIMP + tumors, related to BRAF V600E mutations and MLH1 promoter methylation, are usually associated with low cancer-specific mortality, mostly due to their natural immunogenicity [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The CIMP subtype exists with and without MSI, both showing distinct morphologic, molecular and most importantly, clinical characteristics [ 3 ]. MSI-high/CIMP + tumors, related to BRAF V600E mutations and MLH1 promoter methylation, are usually associated with low cancer-specific mortality, mostly due to their natural immunogenicity [ 3 ]. By contrast, CIMP without MSI is independently related to significantly worse outcome [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation